Enhancing Delirium Recognition: A 4AT Implementation Audit by the Mental Health Liaison Team at Southend Hospital - Roxana Farcasan; Mohamed Ibrahim; Fiona McDowall (BJPsych Open)
Aims: This audit aimed to increase the use of the 4AT (4 A’s Test) within the Mental Health Liaison Team (MHLT) at Southend Hospital to enhance delirium awareness and recognition, thereby facilitating early discharge and improving patient outcomes. The 4AT is a validated and sensitive delirium detection tool, specifically designed for ease of clinical use, and supported by extensive diagnostic accuracy data from over 24 studies involving more than 5,000 observations. It is particularly useful as it can be administered to patients who are too sleepy or restless for traditional cognitive testing. Despite its advantages, compliance with 4AT documentation within the MHLT was initially low.